Study of ovarian reserve parameters in infertile women of different age groups - Valvekar, Umakant; Lakshmi, Santhana; Kumar, Amar Nagesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Main causes of infertility include diminished ovarian reserve. Diminished ovarian reserve is about availability of number of good quality pre ovulatory oocytes in the ovaries. As a woman ages, her ovarian reserve decreases. In recent years assessment of “ovarian reserve” became a strategy in treatment of female infertility. Although the true and functional ovarian reserves reflect different stages of follicular development, they are inherently linked and both decline in parallel with increasing age. Accurate measurement of the ovarian reserve has long been a quest in reproductive medicine. The objective of the study was to find out the ovarian reserve and also to correlate the ovarian reserve indicators with different age groups of infertile women. Methods: This prospective study was conducted at Karpaga Vinayaga Institute of Medical Sciences, Madhurantagam, Chennai, Tamilnadu, India during the period of January 2014 to April 2016. The study comprises of 100 newly diagnosed PCOS women and they were all divided into three age groups. Group I consists of infertile women who were under the age of 26 years or less than 26 years. Group II consists of infertile women of age range between 27 to 35 years. Group III consists of infertile women who are 36 years and greater than 36 years of age. Results: In the present study, ovarian reserve markers had shown significant variation with age in infertile women. Of the markers considered, progesterone, anti-mullerian hormone (AMH) and antral follicle count (AFC) exhibited significant correlation with age. Luteinizing hormone (LH), follicle-stimulating hormone (FSH) with AFC did not show any significant association with age compared to AMH, progesterone and AFC. Conclusions: Our study results also indicate that serum AMH measurement is better predictor for the number of early antral follicles than conventional hormone measurements. Using AMH measurement in combination with AFC may improve the assessment of ovarian reserve for evaluating the fertility potential and monitoring infertility treatment.